Minimally invasive versus open McKeown esophagectomy for patients with esophageal squamous cell carcinoma after neoadjuvant PD-1 inhibitor plus chemotherapy - Chen, Qiuming; Mo, Shaocong; Aizemaiti, Rusidanmu; Cheng, Jun; Wu, Ziheng; Ye, Peng (Frontiers in Oncology, 2023)
Introduction: The purpose of this study was to compare short and mid-term outcomes in esophageal squamous cell carcinoma (ESCC) patients undergoing open or minimally invasive McKeown esophagectomy (MIE) after neoadjuvant PD-1 inhibitor plus chemotherapy. Methods: Patients with locally advanced ESCC underwent open or minimally invasive McKeown esophagectomy after neoadjuvant PD-1 inhibitor plus chemotherapy were retrospectively included from June 2019 to June 2021. The baseline characteristics, pathological data, short-and mid-term outcomes were collected and compared based on the surgical approach. Results: A total of 35 patients were included in the study. An open procedure was performed for 13 patients (37.1%), and 22 (62.9%) patients underwent MIE after neoadjuvant therapy. Compared with open group, MIE group had shorter operative times (350.8± 117.8 vs. 277.9 ±30.2 min, P = 0.009). The total number of resected lymph nodes was not significantly different, but more left recurrent laryngeal lymph nodes were harvested from the Open group (2.6 ± 3.2 vs. 0.9 ± 1.7, P = 0.047). The median follow-up time was 1.42 years (range, 0.35–2.59 years) from the first day of treatment. Three patients (8.6%) died during follow-up, one in the open surgery group and two in the MIE group. There were six (17.1%) patients developed recurrence, three in each group. The 2-year cumulative survival rates were 92.3 ± 7.4% and 89.5 ± 7.1% for the open and MIE groups, respectively. Overall survival was not different between the two surgical approaches. Conclusions: MIE might be safe and feasible for patients with locally advanced ESCC undergoing neoadjuvant PD-1 inhibitor plus chemotherapy.